Care networks of home-dwelling older adults in the Netherlands: proof of concept of a network typology - Kemper-Koebrugge, Wendy; Adriaansen, Marian; Laurant, Miranda; Wensing, Michel (BMC geriatrics, 2023)
Studies on care networks of home-dwelling older adults often focus on network composition. However, looking at network mechanisms (negotiation, navigation and contagion) can be helpful to improve the support generated by the care network. A European study on diabetes patients identified network types based on interaction, which can be beneficial (generative, proxy) or detrimental (struggling, avoidant) to support. This study explored whether these network types are present in care networks of home-dwelling older adults in the Netherlands, and how these types manifest in composition or mechanisms.